Competition Policy in the European Film Industry Focused on Consumers' Interests – a Romanian Perspective - Puiu Nistoreanu; Violeta Mihaela Dinca; Andreea Fortuna Șchiopu (Amfiteatru Economic Journal, 2017)
European cinema was and still is often assimilated by film consumers as art cinema which is more difficult to understand and ultimately to reach a big number of consumers. The objectives of this paper were to examine the pathway of European cinema market and the relationship with its consumers along with their interests and attitudes towards European films and to research the most important measures taken by European Union institutions under their competition policy to support European films through state aid schemes. In order to give shape to these objectives, in-depth interviews with five elite specialists from the Romanian film industry were used, specialists who possess international expertise and recognition. The problems of the qualitative research are: the modification of consumer behaviour face to European cinema and support measures. The findings suggest that regarding its relationship with consumers and their interests in the seventh art, European cinema faces many different difficulties ranging from the competition with American films and insufficient funds, to the increased comfortableness or coziness of the movie consumers of our times. The paper concludes with examples of measures suggested by the respondents, to help European cinema become more attractive to consumers, measures which are already being implemented by the industry, making the results of our study useful for policy and decision makers within this cultural area.
Keywords: A14; D18; L41; Z10; Z18; 330; European film industry; competition for European cinema; European Union state aid; European consumer of cinema